The Influence of Company Characteristics and Political Connections on Tax Avoidance in Manufacturing Companies Listed on the IDX in 2018-2021 - Jefry Prabowo; Isnani Yuli Andini (Formosa Journal of Sustainable Research, 2023)
This study aims to explore the relationship between political ties, profitability, and leverage. tax evasion.Using a purposive sampling technique, this study was conducted between 2018 and 2021 on manufacturing companies listed on the Indonesia Stock Exchange., obtaining 67 companies as research samples. Using EViews version 12, panel data regression was the testing method employed in this investigation.The study's findings suggest that tax evasion is influenced by political ties, profitability, and leverage all at the same time. In part, the profitability variable has a negative effect on tax avoidance (tax avoidance), the leverage variable has a positive effect on tax avoidance (tax avoidance) and the political connection variable has no effect on tax avoidance (tax avoidance)